Determinan Kejadian Berhenti Pakai (Drop Out) Alat Kontrasepsi - Widyawati, Sigit Ambar; Siswanto, Yuliaji; Najib, Najib (HIGEIA (Journal of Public Health Research and Development), 2020)
Abstrak Latar Belakang: Keluarga Berencana adalah upaya mengatur kelahiran anak, jarak dan usia ideal melahirkan, mengatur kehamilan. Salah satu indikator penting untuk mengukur kualitas pemakaian alat/cara KB adalah berhenti pakai (drop out) yaitu kejadian berhentinya menjadi akseptor pada PUS yang sebelumnya sudah menjadi akseptor KB. Tujuan Penelitian: Umengetahui faktor determinan kejadian berhenti pakai alat kontrasepsi pada PUS 10–49 tahun pada tahun 2017. Metode Penelitian: Penelitian deskriptif menggunakan data sekunder daari SDKI Jateng Tahun 2017. Populasi adalah Pasangan Usia Subur (PUS) dengan status kawin yang berusia 10–49 tahun. Sampel adalah 3.414 PUS yaitu pasangan usia subur usia 10–49 tahun dengan status kawin, pernah menggunakan dan masih menggunakan kontrasepsi di Jawa Tengah.. Analisa menggunakan analisa deskriptif dengan uji korelasi Chi Square menggunakan program SPSS versi 17. Hasil: Ada hubungan yang signifikan antara kejadian drop out dengan tingkat pendidikan, tidak ada hubungan yang signifikan antara kejadian drop out dengan tingkat kesejahteraan pada PUS di Jawa Tengah. Simpulan: Tingkat pendidikan merupakan determinan kejadian berhenti pakai (drop out) alat kontrasepsi di Jawa Tengah. Keywords : contraception,couples of childbearing, drop out Abstract Background: Family Planning is an effort to regulate child birth, distance and ideal age for childbirth, regulate pregnancy. One of the important indicators for measuring the quality of use of methods is to stop using, namely the occurrence of cessation of being an acceptor in an Fertilage Age (EFA) who has previously been a family planning acceptor. Research Objectives: To find out the determinant factors of the incidence of stopping contraception at EFA 10–49 years in 2017. Research Method: Descriptive study using secondary data from the Central Java Year 2017. Population this research are couples of childbearing age 10–49 years who are married as much 3,414. Sample in this research are all couples of childbearing age of 10–49 years with marital status, have used and still use contraception in Central Java. The analysis uses descriptive analysis with Chi Square correlation test using SPSS version 17. Results: There was a significant relationship between the incidence of drop out and the level of education, there was no significant relationship between the incidence of drop out and the level of welfare at EFA in Central Java. Conclusion: Educational level is a determinant of the incidence of drop out in contraception in Central Java. Keywords : contraception, couples of childbearing, drop out